BIOCHEMICAL ANALYSIS OF SALIVARY MALONDIALDEHYDE LEVELS IN 14-15-YEAR-OLD ADOLESCENTS WITH ORAL PATHOLOGY - Alexandra Mihaela Stoica; Oana Elena Stoica; Alexandru Vlasa; Cristina Ioana Bica; Liana Bereșescu; Zsuzsanna Bardocz-Veres; Monica Dana Monea (Romanian Journal of Oral Rehabilitation)
Elevated oxidative stress can contribute to inflammation, which is believed to play a role in oral manifestation such as GT or AU mainly in ages of 14 and 15 years. During this period, children are undergoing various physical, mental, and emotional changes due to their transition from childhood to adolescence. As GT or AU are more frequent in this ages, our aim of the study was to determine if there is any positive correlation between the salivary levels of Malondialdehyde (MDA) considered a biomarker of oxidative stress and the severity and progression of mucosal pathology. Materials and methods: Using the High-Performance Liquid Chromatography (HPLC) technique, we assessed the MDA concentrations which were statistically evaluated and compared between a study group of participants diagnosed with GT or AU and a control group of healthy age-matched subjects. Results: The study group has a significantly higher mean value (26.285) compared to the control group (21.425), with a p-value of 0.0017, indicating a statistically significant difference between the two groups. However, the gender distribution between the study group (51.4% female, 48.5% male) and the control group (52% female, 48% male) does not significantly differ, as evidenced by a p-value of 0.9016. Conclusions: The levels of salivary MDA were higher in the study groups with GT and AU, with statistically significant differences (p<0.05) compared to healthy subjects, which questions weather oxidative stress might be linked to geographic tongue pathogenesis or aphthous ulcers.